Clinical outcomes following stereotactic radiosurgery for brain metastases from sarcoma primaries: An international multicenter analysis - Singh, Raj; Roubil, John G; Bowden, Greg; Mathieu, David; Carrier, Louis; Shepard, Matthew; Kite, Trent; Wegner, Rodney E; Picozzi, Piero; Franzini, Andrea; Yang, Huai-Che; Lee, Cheng-Chia; et al. (Cancer, 2025)
BACKGROUND: There is a paucity of data on treatment outcomes following stereotactic radiosurgery (SRS) for brain metastases from sarcoma primaries. METHODS: The International Radiosurgery Research Foundation member-sites were queried for patients with brain metastases from sarcoma primaries treated with SRS. Overall survival (OS) and local control (LC) were calculated via Kaplan-Meier analysis. Univariate analyses examined prognostic factors associated with LC and OS via log-rank t-tests and multivariate analyses (MVA) via Cox proportional hazards model. RESULTS: A total of 146 patients with 309 brain metastases were identified. Two-hundred and thirty lesions were treated with single-fraction SRS with a median dose of 20 Gy (15-24 Gy). Ninety-five patients had extracranial metastases, including 75 oligometastatic patients. One- and 2-year OS and LC rates were 47.7% and 37.3%, and 78.3% and 62.2%, respectively. On univariate analyses, superior 1-year OS was noted among leiomyosarcomas (69.7% vs. 42.6%; p = .02) with poorer outcomes among pleomorphic histologies (10.5% vs. 50.7%; p = .002). Pleomorphic histologies were associated with poorer OS on MVA (hazard ratio [HR], 3.13; p = .006). On MVA, LC was inferior among patients of age ≥45 years (HR, 3.78; p < .001) and superior among leiomyosarcomas (HR, 0.31; p = .03). OS was prognosticated based on adverse factors (ie, nonleiomyosarcoma histology and progressive extracranial metastases). Two-year OS for patients with and without adverse features were 78.6% and 31.5%, respectively. CONCLUSIONS: LC outcomes were driven by histology and age with superior LC among leiomyosarcomas and patients of age <45 years. OS was driven by nonleiomyosarcoma histology and the presence of progressive extracranial disease.
Keywords: výsledek terapie; Young Adult; Brain Neoplasms; Male; overall survival; retrospektivní studie; sarcoma primary; mladý dospělý; nádory mozku; prognóza; Kaplan-Meier Estimate; local control; Adult; Kaplanův-Meierův odhad; Aged; dospělí; mužské pohlaví; senioři; radiochirurgie; sarkom; stereotactic radiosurgery; Treatment Outcome; senioři nad 80 let; lidé; ženské pohlaví; Humans; Sarcoma; Aged, 80 and over; Radiosurgery; Prognosis; brain metastases; Retrospective Studies; Female; lidé středního věku; Middle Aged